Studi Kuantitatif tentang Pengaruh Citra Merek, Promosi, dan Kualitas Produk terhadap Keputusan Pembelian Produk Skincare - Yuniawaty, Yunni; Istichanah, Istichanah; Dewi W, Christina; Azmi, Nurul (Journal of Trends Economics and Accounting Research, 2025)
This study aims to determine the Influence of Brand Image on Purchasing Decisions on The Originote skincare products partially. To determine the Promotion on Purchasing Decisions on The Originote skincare products partially. To determine the Influence of Product Quality on Purchasing Decisions on The Originote skincare products partially. To determine the Influence of Brand Image, Promotion, and Product Quality on Purchasing Decisions on The Originote skincare products simultaneously. The analysis method in this study is to use primary data in the form of distributing questionnaires. The population in this study were students of the Management Study Program, Gunadarma University, Class of 2022 with a sample of 100 respondents. Data analysis using SPSS, through validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regressions, T tests, F tests, and coefficients of determination. The results of the study showed that the influence of promotion partially did not have a significant effect on Purchasing Decisions on The Originote Skincare products. Meanwhile, the Brand Image and product quality variables have a significant effect on Purchasing Decisions on The Originote Skincare products. In addition, the results of the study also show that the variables Brand Image, Promotion and Product Quality have a simultaneous effect on purchasing decisions on The Originote Skincare products.